The Correlation of Body Mass Index and Menstrual Patterns with the Incidence of Anemia in Adolescent Girls - Alit Armini, Ni Ketut; Ayu Wulandari, Icha; Nastiti, Aria Aulia; K Gauda, Amel Dawod; Triharini, Mira (Gaceta Médica de Caracas, 2026)
Introduction: Anemia in adolescent girls is a significant health problem. Adolescent girls are at a higher risk of anemia due to inadequate nutritional intake and excessive blood loss caused by abnormal menstrual patterns. This study aimed to examine the associations among body mass index (BMI), menstrual patterns, and anemia incidence in adolescent girls.